Diagnostic efficacy of 18F-FDG-PET or PET/CT in breast cancer with suspected recurrence: a systematic review and meta-analysis. Issue 11 (November 2016) - Xiao, Yu; Wang, Ling; Jiang, Xuehua; She, Wei; He, Li; Hu, Gang
Abstract : Objectives: The early detection of suspiciously recurrent breast cancer is of significant importance. The aim of the present meta-analysis was to evaluate the overall diagnostic accuracy of fluorine-18 fluorodeoxyglucose ( 18 F-FDG)-PET or PET/computed tomography (CT) for the detection of relapse in suspected recurrent breast cancer. Materials and methods: Medline, Embase, Web of Science, and Cochrane databases were searched for articles on suspiciously recurrent breast cancer and 18 F-FDG-PET or PET/CT up to 10 January 2016. Pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio, and area under the curve (AUC) were calculated. A meta-regression analysis was carried out to explore potential sources of heterogeneity. Results: A total of 26 studies with 1752 patients with suspiciously recurrent breast cancer were included for the analysis; among these, 56.8% because of elevation of tumor markers, in 33.9%, there was suspicion on conventional imaging modalities, and in 9.4%, suggestive clinical symptoms or physical examinations were found. The pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio of 18 F-FDG-PET or PET/CT were 0.90 [95% confidence interval (CI), 0.88–0.90], 0.81 (95% CI, 0.78–0.84), 4.64 (95% CI, 3.50–6.14), 0.12 (95% CI, 0.08–0.16), and 46.52 (95% CI, 29.44-73.51), respectively. In addition, the overall AUC of 18 F-FDG-PET or PET/CT was 0.9358. Meta-regression analysis showed that type of imaging modality (PET over PET/CT) might be a potential source of heterogeneity ( P =0.0799). Furthermore, a subgroup analysis indicated that PET/CT appeared to harbor more specificity in the diagnosis of recurrent breast cancer (0.823 vs. 0.796, P =0.035). The increased AUC suggested increased accuracy of PET/CT over PET (0.9477 vs. 0.9111). Conclusion: 18 F-FDG-PET, and in particular 18 F-FDG-PET/CT, seemed to be a more valuable supplement to current surveillance techniques to detect relapse in suspected recurrent breast cancer patients.